PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP KELENGKAPAN PENGUNGKAPAN LAPORAN TAHUNAN PERUSAHAAN PERBANKAN (Students' Journal of Accounting and Banking, 2012)
This research has been done to know how disclosure level of annual reports in Indonesian stock exchange, and to research what factors might give significant and statistical influence. Those factor, as independent variables are profitability, leverage, liquidity, ownership structure, and age of company. While as dependent variables in disclosure level by giving scores to mandatory and voluntary disclosure. The technique of sampling is taken by purposive sampling method, with samples of banking company annual reports from year 2008-2010 in Indonesian stock exchange. There are 18 companies. The data process and analysis use the technique of multiple linier regression, with the help of SPSS 16.0 for windows program.Keywords: mandatory disclosure, voluntary disclosure, size of company, profitability, leverage, liquidity, ownership structure, age of company